Bridging Emotional Intelligence: Applications in Psychology through the Schutte Emotional Intelligence Scale (SEIS) in Thai Private Hospital Customers - Chokpiriyawat, Thanuset; Siriyota, Kampanat (International Review of Management and Marketing, 2024)
This study explores the implications of emotional intelligence (EI) in marketing communication. The research aims to bridge these disciplines by applying the Schutte Emotional Intelligence Scale (SEIS) in service marketing. The study employs the 33-item SEIS, translated and culturally adapted for use in Thai. The multistage sampling of 600 respondents explores Confirmatory Factor Analysis confirmed four dimensions with acceptable reliability and validity: χ2/df = 2.467, GFI = .909, CFI = .961, RMSEA = .049, and SRMR = .029. This research bridges EI’s theoretical and practical applications in psychology and marketing communication, emphasising EI’s role in shaping consumer experiences and improving customer relationships. It also enhances its cultural relevance for future research and applications.